Effects of Audit Fee, Audit Delay, Financial Distress, Audit Opinion and Audit Tenure on Auditor Switching - Dewi, Rizqi Tiwi Kusuma; Rahayu, Sri; Ridwan, Muhammad (Journal of Business Management and Economic Development, 2023)
This study aims to analyze the Effect of Audit Fee, Audit Delay, Financial Distress, Audit Opinion and Audit Tenure on Auditor Switching (Empirical Studies of Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2019-2021) partially and simultaneously. This research data uses secondary data in annual reports of company on the Indonesia Stock Exchange (IDX) and the official website of the related company. The sample of this research is a Manufacturing Company in the Food and Beverage Sub Sector using a purposive sampling technique in taking the sample so that there are 21 samples with 3 years of observation (63 observations). The analysis technique used is logistic regression analysis technique using the SPSS 25 software application. The results of the R2 test show that the effect of the independent variable on the dependent variable is 71.9% and 28.1% is explained by other variables. Based on the test result, it is known that the variables Audit Fee, Audit Delay, Financial Distress, Audit Opinion and Audit Tenure simultaneously have a significant effect on Auditor Switching. The results showed that the variables of financial distress, audit opinion and audit tenure partially had a significant effect on auditor switching, while the variables audit fees and audit delay partially had no significant effect on auditor switching.